2015
DOI: 10.1083/jcb.201503019
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell autophagy, myelinophagy, initiates myelin clearance from injured nerves

Abstract: Schwann cells degrade myelin after injury by a novel form of selective autophagy, myelinophagy, which is positively regulated by the JNK/c-Jun pathway and is defective in the injured central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
384
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(421 citation statements)
references
References 47 publications
16
384
1
1
Order By: Relevance
“…Although not significant, the proportion of autophagy structures had also decreased in unmyelinated axons while it was increased in Schwann cells at follow-up. Indeed, it has recently been reported that Schwann cells use autophagy as a degradation process (Gomez-Sanchez et al, 2015;Jang et al, 2016). Obviously, the autophagy pathway is affected in both axons and Schwann cells in longterm diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although not significant, the proportion of autophagy structures had also decreased in unmyelinated axons while it was increased in Schwann cells at follow-up. Indeed, it has recently been reported that Schwann cells use autophagy as a degradation process (Gomez-Sanchez et al, 2015;Jang et al, 2016). Obviously, the autophagy pathway is affected in both axons and Schwann cells in longterm diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells in the distal nerve stump lose their axonal attachment, proliferate and resorb myelin. Autophagy of myelin by Schwann cells provides the rate-limiting mechanism for myelin clearance and depends on JNK/c-Jun (Gomez-Sanchez et al, 2015). The initial signal for the Schwann cell response appears to be provided by axons, as Wallerian degeneration slow (Wlds) mouse mutants whose axon destruction is delayed also show gross delays in myelin removal and nerve regeneration.…”
Section: Nrg1 and Remyelination After Injurymentioning
confidence: 99%
“…To test whether autophagy is necessary for Schwann cell degradation of myelin after nerve crush injury, as has recently been shown after nerve transection, we generated mice in which Schwann cells are unable to perform autophagy due to deletion of essential autophagy protein atg7 (floxed Atg7 × P0 Cre) (20)(21)(22). These mice did not display any obvious behavioral abnormalities before their use for experiments at 8 to 12 wk of age.…”
Section: Assessment Of the Role Of Autophagy In Myelin Debris Clearancementioning
confidence: 99%